ANALYSIS OF POTENTIAL OF GREENHOUSE GASES EMISSIONS REDUCTION IN UKRAINE - Zaporozhets, Oleksandr I.; Movchan, Yaroslav I.; Galperina, Liubov Р.; Stranadko, Natalia V.; Loyik, Iryna V. (Proceedings of National Aviation University (archive), 2010)
There was conducted the analysis of measures on greenhouse gases emissions reduction according to various Ukrainian economic development scenarios, assessment of greenhouse gases emissions reduction potential until 2020 and proposed approaches for the development of mitigation to climate change.